To solve the inequality \((x - 14)(x - 17)(x + 14) \geq 0\), we first find the critical points by setting each factor equal to zero.
- \(x - 14 = 0 \) gives \(x = 14\)
- \(x - 17 = 0\) gives \(x = 17\)
- \(x + 14 = 0\) gives \(x = -14\)
Thus, the critical points are \(x = -14\), \(x = 14\), and \(x = 17\).
Next, we'll determine the sign of the expression \((x - 14)(x - 17)(x + 14)\) in the intervals defined by these critical points:
- \((- \infty, -14)\)
- \((-14, 14)\)
- \((14, 17)\)
- \((17, \infty)\)
Test the intervals:
-
Interval \((- \infty, -14)\): Choose \(x = -15\). \[ (-15 - 14)(-15 - 17)(-15 + 14) = (-29)(-32)(-1) < 0 \]
-
Interval \((-14, 14)\): Choose \(x = 0\). \[ (0 - 14)(0 - 17)(0 + 14) = (-14)(-17)(14) > 0 \]
-
Interval \((14, 17)\): Choose \(x = 15\). \[ (15 - 14)(15 - 17)(15 + 14) = (1)(-2)(29) < 0 \]
-
Interval \((17, \infty)\): Choose \(x = 18\). \[ (18 - 14)(18 - 17)(18 + 14) = (4)(1)(32) > 0 \]
Summary of intervals:
- In \((- \infty, -14)\), the expression is negative.
- In \((-14, 14)\), the expression is positive.
- In \((14, 17)\), the expression is negative.
- In \((17, \infty)\), the expression is positive.
Include the critical points:
At the critical points \(x = -14\), \(x = 14\), and \(x = 17\), the expression equals zero:
- \((x - 14)(x - 17)(x + 14) = 0\)
Solution:
From our tests, the expression is non-negative in the intervals:
- \([-14, 14]\)
- \([17, \infty)\)
Combined, the solution in interval notation is: \[ [-14, 14] \cup [17, \infty) \]
Final answer:
B. The solutions are the values of \(x\) in the interval \([-14, 14] \cup [17, \infty)\).